Effects of Bone Marrow Aspirate Concentrate on Radiographic Integration of Femoral Condylar Osteochondral Allografts. Issue 7 (21st July 2017) - Stannard, James P.; Oladeji, Lasun O.; Cook, Cristi; Kfuri, Mauricio; Crist, Brett D.; Smith, Matthew Jared; Cook, James L.
Objectives: Symptomatic articular cartilage lesions of the femoral condyles are a common problem in athletes. For large (>2.5 cm 2 ) lesions, fresh osteochondral allograft (OCA) transplantation is a good option based on 88% return to sport and >75% 10-year survival. Lack of graft survival typically results from loss of cartilage integrity or inadequate integration of graft bone into the patient. Because OCA bone integration occurs via creeping substitution, methods for speeding and enhancing OCA bone integration to mitigate failures are highly desirable. Bone marrow aspirate concentrate (BMAC), which contains osteoprogenitor cells and osteoinductive proteins, has the potential to accelerate and promote OCA bone integration. Therefore, this study was designed to test the hypothesis that BMAC treatment of large femoral condylar OCAs would be associated with superior radiographic OCA bone integration compared to non-treated allografts during the critical first 6 months after surgery. Methods: An IRB-approved review of patients enrolled in a prospective registry who were treated with large OCA transplants to one or both femoral condyles at our institution from March 12, 2013 to March 14, 2016 was performed. Patients were excluded if they did not have orthogonal view radiographs performed at 6 weeks, 3 months, and 6 months postoperatively. Each condyle undergoing OCA transplantation was assessed individually by an independent musculoskeletal radiologist blinded to treatment group and time point. OCAs were assessed with respect to graft integration (0-100% integrated into patient bone) and degree of sclerosis of the graft (0 - normal, 1 - mild sclerosis, 2 - moderate sclerosis, 3 - severe sclerosis) at each time point. Data were compiled into two groups based on treatment with BMAC (OCA bone saturated with autogenous BMAC immediately prior to implantation) versus no BMAC treatment and analyzed for statistically significant (p<0.05) differences. Results: This study identified 16 condyles in 15 patients receiving large OCA transplants without BMAC and 23 condyles in 21 patients receiving large OCA transplants with BMAC. There were no significant differences in patient age, gender, BMI, ASA or proportions of lateral versus medial condyles, patients with diabetes, or smokers. The BMAC group had significantly (p<0.033) higher graft integration scores at 6 weeks, 3 months and 6 months after surgery (Table). Graft sclerosis was significantly (p<0.017) less in the BMAC group at 6 weeks and 3 months with no significant difference 6 months after surgery (Table). When combining treatment cohorts to examine the influence of smoking on graft integration, non-smokers had significantly (p=0.007) higher graft integration scores at 6 months (Table). There were no statistically significant differences in graft integration between smokers and non-smokers in the BMAC group. One bone healing complication occurred in a smoker receiving an OCA that was not treated with BMAC, while no bone healing complications occurred in the BMAC group. Conclusion: Large femoral condylar osteochondral allografts treated with autogenous bone marrow aspirate concentrate prior to implantation showed superior radiographic integration to patient bone and less sclerosis during the initial 6-month postoperative period. BMAC treatment of osteochondral allografts may mitigate failure of osteochondral allograft bone healing. Table – Graft Integration Scores Cohort Time Point Graft Integration P-value Sclerosis P-value BMAC 6 weeks 43.1 ± 22.8 0.03 1.4 ± 0.6 0.016 No BMAC 25.6 ± 25 1.9 ± 0.6 BMAC 3 months 67.2 ± 17.9 0.033 1.2 ± 0.5 0.017 No BMAC 50.6 ± 28.9 1.7 ± 0.7 BMAC 6 months 84.1 ± 8.4 0.017 0.9 ± 0.5 > 0.05 No BMAC 74.4 ± 15.9 1.2 ± 0.5 Smokers 6 months 83.7 ± 8.2 0.007 Non-Smokers 72.1 ± 17.5